"That is just your stuff": The potential use and abuse of congruence in counselling and psychotherapy practice and training. Issue 2 (7th February 2023) - Jones, Callum
Abstract: This piece discusses the potential use and misuse of congruence within counselling training and practice. A definition of congruence is provided, and how deliberate misuse of congruence could result from two separate emotional communications (bullying and gaslighting) is discussed. Current representations and misrepresentations of congruence in counselling and psychotherapy have been highlighted. A new term of "Intentional Congruence Misuse" was coined to explain this position (not to be confused with incongruence). "Intentional Congruence Misuse" is the deliberate bullying of another individual using terms related to congruence. A discussion has been provided to emphasise the evident implications for counselling, psychotherapy practice and training. The author acknowledges that this opinion piece will be from a biased perspective. Still, it does not aim to detract from others who have found their therapy and counselling training beneficial.